Use substutution to solve the system. \[ \begin{array}{r}-2 x+3 y=6 \\ 3 x-5=y\end{array} \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To use substitution, we can solve the second equation for \( y \): \[ y = 3x - 5. \] Now we can substitute \( y \) in the first equation: \[ -2x + 3(3x - 5) = 6. \] This simplifies to: \[ -2x + 9x - 15 = 6, \] which gives: \[ 7x - 15 = 6. \] Next, we add 15 to both sides: \[ 7x = 21. \] Finally, we divide by 7: \[ x = 3. \] Now we substitute \( x = 3 \) back into the equation for \( y \): \[ y = 3(3) - 5 = 9 - 5 = 4. \] Thus, the solution to the system is: \[ (x, y) = (3, 4). \]